2018
DOI: 10.3390/en11030504
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Diesel-Fuel Replacement by Crude Palm Oil in Indonesian Power Plants

Abstract: Indonesia needs to find an alternative fuel to substitute diesel in their power plants in order to reduce the use of nonrenewable energy sources. The Indonesian government has a target to reduce oil fuel consumption while improving the efficiency of energy utilization. Crude palm oil is proposed to be used for this substitution. In this paper, the authors conduct an economic analysis of the replacement of diesel by crude palm oil. To predict future prices, a time series analysis is conducted using AutoRegressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Analysis of the energy potential and environmental protection of four types of biomass (wheat straw, oat grains, larch needles and rapeseed pods) was experimentally investigated in Reference [12]. The use of alternative fuels (such as crude palm oil or crude rubber seed oil) instead of diesel for energy production in Asia, as a measure to reduce the use of nonrenewable fuels and improve energy efficiency, was experimentally analyzed by the authors of [13] and economically investigated by the authors of [14]. An efficient proven technology for the co-combustion of biomass and hydrogen-rich gas (HRG) was demonstrated in Reference [8].…”
Section: Propertiesmentioning
confidence: 99%
“…Analysis of the energy potential and environmental protection of four types of biomass (wheat straw, oat grains, larch needles and rapeseed pods) was experimentally investigated in Reference [12]. The use of alternative fuels (such as crude palm oil or crude rubber seed oil) instead of diesel for energy production in Asia, as a measure to reduce the use of nonrenewable fuels and improve energy efficiency, was experimentally analyzed by the authors of [13] and economically investigated by the authors of [14]. An efficient proven technology for the co-combustion of biomass and hydrogen-rich gas (HRG) was demonstrated in Reference [8].…”
Section: Propertiesmentioning
confidence: 99%
“…Other authors discuss energy investments in Indonesia. For example, according to [75], investment into diesel replacement with palm oil showed positive net present values and quicker payback period thanthe project analyzed in this paper. For China, Deng et al, [76] calculated the cost efficiency of Jatropha Curcas biodiesel with positive results albeit with a smaller discount rate.…”
Section: Resultsmentioning
confidence: 70%
“…Murti emphasized that the higher prices of crude oil increase the competitiveness of biodiesel as an alternative to fossil diesel and subsequently lift demand for palm oil (Murti, 2017). Prochazka and Honig (2018), in their economic analysis of replacing dieselfuel by crude palm oil in Indonesian power plants on the back of international diesel price evolution, showed that the move may be profitable given the increasing prices of diesel and the weakening Indonesian currency against the US dollar (Prochazka & Honig, 2018). Since high global oil prices increase the attractiveness of biofuel, they also drive the biofuel prices because of improved demand.…”
Section: Global Fuel Prices Affecting the Biodiesel Economicsmentioning
confidence: 99%